Pendampingan Pembuatan Produk Gel Pengharum Ruangan Aroma Lavender di MTsN 1 Palangka Raya - Anis Rosida; Jumrodah Jumrodah (Kolaborasi : Jurnal Hasil Kegiatan Kolaborasi Pengabdian Masyarakat, 2025)
This community service program aimed to enhance students’ knowledge and awareness regarding the use of natural ingredients in producing lavender-scented air freshener gel as a safe and environmentally friendly alternative. The activity employed an educational outreach approach, combining material presentations, video demonstrations, and direct observation of product samples. The program engaged 32 eighth-grade students at MTsN 1 Palangka Raya. Through these activities, students learned about the various natural ingredients used in the gel, the functional properties of each ingredient, and the environmental and health benefits of lavender aromatherapy. The results of the program indicated significant improvements in students’ understanding of gel production concepts and their ability to identify the characteristics of the products during observation. Students showed high enthusiasm for using natural ingredients in household products, which also contributed to enhancing their environmental literacy. Furthermore, the program provided MBKM students with valuable experience in delivering applied science education. The success of this program not only fostered students' awareness of sustainable practices but also provided an engaging learning experience. Based on the positive outcomes observed, the program is recommended for replication in other schools, with the addition of hands-on practice sessions to further reinforce the concepts learned.